Impact of Water Hyacinth Compost and Compound Fertilizers on Soil Chemistry, Nutrient Uptake, and Shallot Yield - Salsabilla, Annisya; Sofyan, Emma Trinurani; Yuniarti, Anni (Jurnal Ilmu Pertanian, 2025)
Water hyacinth (Eichhornia crassipes) compost provides a sustainable opportunity to improve soil fertility while managing an invasive aquatic weed. This study evaluated the optimal combination of water hyacinth compost and NPKS fertilizers for enhancing soil chemical properties, nutrient uptake, and shallot (Allium ascalonicum L.) yield on Inceptisols. The experiment was conducted from July to October 2023 using a Randomized Complete Block Design with seven fertilization treatments, including a control treatment without compost or NPKS, a compost-only treatment, a full NPKS treatment, and four combined treatments consisting of compost at ¼, ½, ¾, and 1 dosage levels each paired with ¾ of the recommended N, P, K, and S fertilizers. Results showed substantial improvements in soil chemistry, particularly in treatments combining compost with reduced mineral fertilizer rates. Soil pH increased toward neutral conditions, total nitrogen rose from 0.10% in the control to 0.32%, and available phosphorus and potassium increased more than fourfold compared with unfertilized soil. The treatment of ¾ compost dose (18.75 t ha⁻¹) + ¾ recommended NPKS consistently produced the highest soil nutrient availability, reflecting enhanced mineralization and nutrient retention. Nutrient uptake by shallot plants also improved markedly, with nitrogen, phosphorus, and potassium absorption increasing two- to threefold relative to the control. These improvements corresponded with clear gains in crop performance: the number of bulbs increased from 5 in the control to 9, and fresh bulb weight rose from 92.89 g to 132.26 g. Integrated treatments outperformed both compost-alone and full mineral fertilization. These findings indicate that combining water hyacinth compost with reduced NPKS fertilization can maintain high shallot productivity while decreasing reliance on chemical fertilizers, enhancing soil fertility, and providing an environmentally beneficial use for invasive aquatic biomass—supporting sustainable and circular nutrient management in low-fertility tropical soils